BOLBITIS NAGALANDENSE R. R. RAO & N. S. JAMIR A NEW SPECIES OF LOMARIOPSIDACEAE FROM NAGALAND, INDIA - Rao, R. R.; JAMIR, N. S. (Research Center for Biology, 1984)
An illustrated description of the new species Bo-lbitis nagalandense is presented